MO1052GREEN DIALYSIS: FROM MITH TO FUTURE. (29th May 2021) - Covella, Bianca; Rossi, Luigi; Corciulo, Simone; Fois, Antioco; Lomonte, Carlo; Piccoli, Giorgina
Abstract: Background and Aims: Over 2 million persons of the 7.8 billion world population undergo hemodialysis (HD). The need is underestimated because dialysis is not available free of charge for more of half of the word population. HD is costly process and produces a large quantity of medical waste. Reducing the environmental burden should be addressed as part of implementation dialysis programs. While collaboration between physicians and several different professionals is needed to design and develop projects in this direction, these are lingering and the literature is still scant. We overviewed literature to frame what is in progress and find clues for development. Method: We conducted a systematic review of the literature from 2000 searching in PubMed, Scopus, Web of Science, and Google Scholar using search keywords including dialysis, green, recycling, ecology. We retrieved 41 publications in medical and technological fields. The results were summarized in a narrative review. Results: Facilities: the points on which attention is focused are the design of new buildings, whose project should encompass green solutions, including solar power and water conservation, to reduce long-term expenses and ensure an eco-friendly development. Water: water consumption remains high, and the essential targets to improve efficiency are the optimization of the reverse osmosis system, and of the dialysate flow rate, and the waste-water management. The current idea is to substitute standard reverse osmosis, which have a high percent of waste-water, with recirculating systems. Likewise, lowering of dialysate flow rate could spare water consumption with no significant difference in term of efficiency. Moreover, different solutions have been proposed to reuse reject water: local sanitation, laundry departments, sterilization units within health facilities using redirected water, landscaping and irrigation. Power: electricity needed per dialysis session is twice the average daily consumption of a family of four people. Use of renewable energies, as solar or wind power, has been proposed, and are occasionally applied to home HD. To date just one attempt has been made to recycling energy by using hydroturbine. Disposable materials: most of dialysis disposables is made of plastic, over half of which is labeled as "potentially hazardous". Only a minimal part of the plastic used in dialysis disposables is recyclable, both because of its composition and its assembly which makes in fact impossible the segregation of the different components. Present research regards bioplastics, new assembling techniques, alternative technologies of incineration, microwave treatment, alkaline hydrolysis, biological treatment and the new steam sterilize-then-shred system. Dialysis machines: at the best of our knowledge there are no studies available about dialysis machine recycling. Personnel education: the role of dialysis staff is essential in recycling and reusing materials as well as in correctly dividing contaminated and non-contaminated waste. Conclusion: The development of sustainable buildings, devices and procedures requires a multidisciplinary approach: medical, chemical, biological, engineering; in addition producers contribution and government regulation are needed. Talking about these issues, involving specialists, spreading the concepts of planet friendly treatments, gives the opportunity to share ideas, experiences and turn them into relevant innovations. A good starting point could be data collection to identify critical issues and outline pragmatic operational possibilities to reduce consumption, increase reuse and recycle, involve and instruct health care personnel, integrate dialysis facilities in the environment they are built in.